Hubungan Tingkat Pengetahuan ,Riwayat Anemia, Dan Pemberian Asi Eksklusif Terhadap Kejadian Stunting Pada Anak Balita Di Wilayah Kerja Puskesmas Teluk Pucung Kota Bekasi - Azzahra Iman Nazwa; Dayuningsih Dayuningsih; Saka Adhijaya Pendit (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Stunting is a chronic nutritional problem that affects a child's physical growth, cognitive development, and long-term health. Factors such as maternal knowledge, history of anemia during pregnancy, and exclusive breastfeeding play a significant role in the incidence of stunting in toddlers. This study aims to determine the relationship between these three factors and stunting in toddlers in the Teluk Pucung Community Health Center (Puskesmas Teluk Pucung) working area, Bekasi City. The method used was quantitative with a cross-sectional design, involving 80 mothers with toddlers at risk of stunting, selected through purposive sampling. Data were collected using a questionnaire and analyzed using Chi-square at a significance level of 0.05. The results showed a significant relationship between maternal knowledge and stunting (p = 0.005), and all three variables were shown to contribute to the overall growth status of toddlers. In conclusion, maternal knowledge, history of anemia, and exclusive breastfeeding practices were significantly associated with the incidence of stunting. These findings are expected to form the basis for developing educational programs, preventing anemia, and increasing the coverage of exclusive breastfeeding optimally.